2017
DOI: 10.1007/978-3-319-69035-3_14
|View full text |Cite
|
Sign up to set email alerts
|

Energy Efficient Scheduling of Application Components via Brownout and Approximate Markov Decision Process

Abstract: Unexpected loads in Cloud data centers may trigger overloaded situation and performance degradation. To guarantee system performance, cloud computing environment is required to have the ability to handle overloads. The existing approaches, like Dynamic Voltage Frequency Scaling and VM consolidation, are effective in handling partial overloads, however, they cannot function when the whole data center is overloaded. Brownout has been proved to be a promising approach to relieve the overloads through deactivating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Xu and Buyya [ 24 ] increase the functionality of the brownout to reduce data center energy consumption. They proposed a brownout-based approximate Markov Decision Process approach to improve tradeoffs between energy-saving and user discounts.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Xu and Buyya [ 24 ] increase the functionality of the brownout to reduce data center energy consumption. They proposed a brownout-based approximate Markov Decision Process approach to improve tradeoffs between energy-saving and user discounts.…”
Section: Related Workmentioning
confidence: 99%
“…Xu et al [23] discuss the brownout model to reduce data center energy consumption. This approach can reduce energy consumption by selectively and dynamically deactivating optional Xu and Buyya [24] increase the functionality of the brownout to reduce data center energy consumption. They proposed a brownout-based approximate Markov Decision Process approach to improve tradeoffs between energy-saving and user discounts.…”
Section: Related Workmentioning
confidence: 99%
“…Moreover, the employee health data, real-time data collection and processing has not been fully addressed since it is challenging to continuously monitor an employee's health [64] [70]. Motivated by the successful applications of IoT [66] [68] 4 [69] in other fields of technological development integrated with the fortes of ML, an IoT based EHIS called IoTPulse has been proposed to predict the alcohol addiction using ML model with high accuracy. An alcohol consumer can be monitored using IoT enabled health monitoring devices.…”
Section: Motivation and Our Contributionsmentioning
confidence: 99%
“…In [13], we presented the brownout enabled system model and proposed several heuristic policies to find the microservices or application components that should be deactivated for energy saving purpose. The results showed that a trade-off existed between energy consumption and discount, and in [14], we adopted approximate Markov Decision Process to improve the trade-off.…”
Section: Related Workmentioning
confidence: 99%
“…The BrownoutCon is designed and implemented by following the brownout enabled system model in our previous works [13] [14]. Mandatory containers and optional containers are introduced in the system model, which are identified according to whether the containers can be temporarily deactivated or not.…”
Section: Introductionmentioning
confidence: 99%